WEED INTERFERENCE IN EGGPLANT CROPS - Marques, Luiz Junior Pereira (2017)
Uncontrolled weed growth interferes with the growth eggplants and crop yields. To control weeds, the main weed species must be identified in crop growing areas and during weed control periods, as weed species might vary in relation to management practices. Therefore, this study aimed to identify the main weed species and determine the periods of weed interference in the eggplant cultivar Nápoli when grown under certain cultural practices, including plant staking and sprout thinning. The experiment was carried out in 2014 using a randomized complete block design, with 3 replications. The treatments consisted of 11 periods of (1) increasing weed control and (2) increasing coexistence of eggplant with weeds from the first day of transplanting (0–14, 0–28, 0–42, 0–56, 0–70, 0–84, 0–98, 0–112, 0–126, 0–140, and up do day 154). Eggplant staking and sprout thinning were performed 42 days after transplanting (DAT). Weed identification and crop yield assessments were performed to determine the Period Before Interference (PBI), Total Period of Interference Prevention (TPIP), and the Critical Period of Interference Prevention (CPIP). The major weeds found in the eggplant cultivar Nápoli were Eleusine indica, Portulaca oleracea, and Cyperus rotundus. Coexistence between the weed community and the eggplant throughout the entire crop production cycle reduced eggplant fruit yield by 78%. The PBI was 29 DAT and the TPIP was 48 DAT, resulting in 19 days of CPIP.